The Prevalence of Smoking, Determinants and Chance of Psychological Problems among Smokers in an Urban Community Housing Project in Malaysia - Abd Rashid, Rusdi; Kanagasundram, Sharmilla; Danaee, Mahmoud; Majid, Hazreen Abdul; Sulaiman, Ahmad Hatim; Ahmad Zahari, Muhammad Muhsin; Ng, Chong Guan; Francis, Benedict; Wan Husin, Wan Azlinda Irnee; Tin, Tin Su (MDPI, 2019)
Objective: This study was conducted to assess the prevalence, pattern of smoking and sociodemographic factors among Kerinchi residents in Kuala Lumpur, as well as to identify the association between smoking, stress, anxiety and depression. Methods: This study was carried out at four community housing projects in the Lembah Pantai area in Kuala Lumpur. Data was collected between 3 February 2012, and 29 November 2012. Data collectors made house visits and used interviewer administered questionnaires containing questions on demographic data and smoking patterns. Depression anxiety stress scale (DASS) was used to assess psychological symptoms. Alcohol smoking and substance involvement screening tool (ASSIST) scale was used to assess nicotine use. Results: Data from 1989 individuals (833 households) showed the age of respondents ranged from 18 to 89 years and the mean age was 39.12 years. There were 316 smokers indicating the prevalence of smoking was 15.85%, with 35.5% among males and 1.8% among females. Further, 86.6% of smokers were Malay and 87% were Muslims. Divorce was associated with smoking. Unemployment and housewives were less associated with smoking. Depression and anxiety were significantly associated with smoking (OR = 1.347. 95% CI: 1.042-1.741) and (OR = 1.401. 95% CI: 1.095-1.793) respectively. Conclusion: Screening for depression and anxiety should be routinely performed in the primary care setting and in population-based health screening to intervene early in patients who smoke. © 2019 by the authors. Licensee MDPI, Basel, Switzerland.